Near rings, fuzzy ideals, and graph theory - Satyanarayana, Bhavanari; Prasad, Kuncham Syam. (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
''Nearrings, Fuzzy Ideals and Graph Theory' is a very fascinating course to learn and show. Nearring Theory has enormous applications in different subject areas like digital computing, sequential mechanics, automata theory, graph theory and combinatorics. The first step towards nearrings was an axiomatic research done by Dickson in 1905. He exhibited that there do exist'fields with only one distributive law'. Nearrings arise in a natural way, take the set M(G) of all mappings of a group (G, +) into itself, define addition'+' and point-wisely and'o' as composition of mappings. Another example is that set of all polynomials with addition and substitution'--
Includes bibliographical references (pages 453-458) and index.
Keywords: Near-rings.; Fuzzy sets; Graph theory